A BNCC na contramão do PNE 2014-2024: avaliação e perspectivas. - Campos, Roselane Fátima (Retratos da Escola, 2018)
AGUIAR, Márcia A. S.; DOURADO, Luiz (Org.). A BNCC na contramão do PNE 2014-2024: avaliação e perspectivas. Recife: ANPAE, 2018.